1995
DOI: 10.1007/bf02445567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adaptation to intermittent hypoxia on oxidative phosphorylation in brain mitochondria of rats with different sensitivities toward oxygen deficiency

Abstract: After long-term adaptation to intermittent hypoxia, rats with an initially low resistance to acute oxygen deficiency were 2 to 4 times more resistant to it, while highly resistant rats did not show a significant change in resistance. The adaptation was accompanied by weakening of the electron-transporting function of the respiratory chain and increasing efficiency of oxidative phosphorylation in the brain mitochondria oxidizing NAD-dependent substrates, indicating that energy was produced in a more economical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…The large number of small mitochondria in the cerebral cortex in tolerant-to-hypoxia rats is an indicator of increased metabolic mitochondrial activity and higher intensity of oxidative phosphorylation in these rats in comparison to susceptible rats. This is in accordance with the results of earlier studies that demonstrated different intensities of oxidative phosphorylation in the cerebral cortex in rats with tolerant and susceptible hypoxia resistance [ 214 , 215 ]. Thus, under normoxia, phenotypic ultrastructural, functional and metabolic differences are observed between the mitochondria of cerebral cortex cells of tolerant- and susceptible-to-hypoxia rats.…”
Section: Physiological Biochemical and Molecular-biological Charsupporting
confidence: 93%
“…The large number of small mitochondria in the cerebral cortex in tolerant-to-hypoxia rats is an indicator of increased metabolic mitochondrial activity and higher intensity of oxidative phosphorylation in these rats in comparison to susceptible rats. This is in accordance with the results of earlier studies that demonstrated different intensities of oxidative phosphorylation in the cerebral cortex in rats with tolerant and susceptible hypoxia resistance [ 214 , 215 ]. Thus, under normoxia, phenotypic ultrastructural, functional and metabolic differences are observed between the mitochondria of cerebral cortex cells of tolerant- and susceptible-to-hypoxia rats.…”
Section: Physiological Biochemical and Molecular-biological Charsupporting
confidence: 93%
“…Hypoxia in mammalian cells is often correlated with a reduction in cytochrome levels and mitochondrial enzyme activities. In addition, respiration rates decrease in brain mitochondria of rats and mice exposed to intermittent hypobaric hypoxia (10,17,35,38). However, the resting and active respiration rates of liver and heart mitochondria isolated from rats acclimatized to hypobaric hypoxia did not differ from those of control rats (11), not even when measured at more physiological low oxygen concentrations (12).…”
Section: Discussionmentioning
confidence: 96%
“…Similar, though less pronounced differences in values of kinetic parameters are typical for cytochrome oxidase in BC of HR and LR animals. Therefore, in the LR BC, these enzymes faster become saturated with the enzyme-specific substrates (NADH or cyt- c ) and slower oxidize them, which may result in lower activity and faster inactivation of C-I (Dudchenko and Luk'yanova, 1995 , 1996 ; Luk'yanova et al, 1995 ).…”
Section: Features Of Respiratory Chain Reprogramming In Hypoxic Brainmentioning
confidence: 99%
“…For this reason, the suppression of BC C-I activity occurs earlier and is more marked in LR rats than in HR rats. Therefore, in different forms of hypoxic exposure, the switching of oxidation pathways for respiratory chain substrates from the NAD-dependent pathway to the succinate pathway is due to kinetic reasons (Luk'yanova et al, 1995 ). The existence of different kinetic properties of respiratory chain enzymes in HR and LR rat BC, a target for hypoxia, suggests that this phenomenon is genetically predetermined, and the energy metabolism is involved as a major factor determining formation of individual resistance.…”
Section: Features Of Respiratory Chain Reprogramming In Hypoxic Brainmentioning
confidence: 99%